Decision-making deficits in patients with chronic schizophrenia: Iowa Gambling Task and Prospect Valence Learning model - Kim MS (Dove Medical Press, 2016)
Myung-Sun Kim,1 Bit-Na Kang,1 Jae Young Lim2 1Department of Psychology, Sungshin Women’s University, Seoul, Republic of Korea; 2Department of Psychiatry, Keyo Medical Foundation, Keyo Hospital, Uiwang, Republic of Korea Purpose: Decision-making is the process of forming preferences for possible options, selecting and executing actions, and evaluating the outcome. This study used the Iowa Gambling Task (IGT) and the Prospect Valence Learning (PVL) model to investigate deficits in risk-reward related decision-making in patients with chronic schizophrenia, and to identify decision-making processes that contribute to poor IGT performance in these patients. Materials and methods: Thirty-nine patients with schizophrenia and 31 healthy controls participated. Decision-making was measured by total net score, block net scores, and the total number of cards selected from each deck of the IGT. PVL parameters were estimated with the Markov chain Monte Carlo sampling scheme in OpenBugs and BRugs, its interface to R, and the estimated parameters were analyzed with the Mann–Whitney U-test.Results: The schizophrenia group received significantly lower total net scores compared to the control group. In terms of block net scores, an interaction effect of group × block was observed. The block net scores of the schizophrenia group did not differ across the five blocks, whereas those of the control group increased as the blocks progressed. The schizophrenia group obtained significantly lower block net scores in the fourth and fifth blocks of the IGT and selected cards from deck D (advantageous) less frequently than the control group. Additionally, the schizophrenia group had significantly lower values on the utility-shape, loss-aversion, recency, and consistency parameters of the PVL model. Conclusion: These results indicate that patients with schizophrenia experience deficits in decision-making, possibly due to failure in learning the expected value of each deck, and incorporating outcome experiences of previous trials into expectancies about options in the present trial. Keywords: IGT, PVL model, risk-reward related decision-making